Cardiomyopathy and thrombogenesis in cats through left atrial morphological and fluid dynamics analysis - Pons, Maria Isabel; Olivares, Andy L.; Mill, Jordi; Matos, Jose Novo; Garcia-Canadilla, Patricia; Cerrada, Inma; Guy, Anna; Morales Ferez, Xabier; Hutchinson, J. Ciaran; Simcock, Ian C.; Arthurs, Owen J.; Cook, Andrew C.; et al. (Scientific reports, 2025)
The relationship between atrial fibrillation (AF), blood flow disturbances and thrombus formation is well-established in humans. Thrombi primarily form in the left atrial appendage (LAA), but the specific role of LAA morphology remains unclear. Felines, despite rarely experiencing AF, present a valuable model for studying human heart diseases. Cats exhibit a high incidence of cardiomyopathies, often accompanied by significant left atrial dilation and thrombus formation. This unique aspect prompts research focusing on LAA morphology and function in relation to thrombus development. Our study, using advanced image processing and fluid simulations on 24 cat hearts ranging from normal to cardiomyopathy subjects, aims to find distinctions in left atrium (LA) and LAA morphologies, blood flow patterns and their relation to thrombus formation. Significantly different variables in feline heart groups included: heart weight, LAA volume, LA volume, ostium area, ostium area-to-heart weight ratio, centreline length and velocity at the LAA ostium. Fluid simulations revealed lower LAA blood flow velocities and increased thrombotic risk in cases with thrombi. Our study enhances the understanding of LAA structure and function, offering insights into thrombus formation mechanisms with potential implications for better managing thrombosis risk in patients.